Transforming central-local government relations and decentralization: A study on China and selected ASEAN nations - Phang, Siew Nooi (Institute of China Studies, University of Malaya, Kuala Lumpur, 2013)
Transformation and reforms in central administration are often influenced by external and domestic factors such as economic growth, human resources, foreign trade and natural assets.Central government needs to adjust to changing circumstances which necessitates assessing its relationship with its sub-national governments. Decentralization becomes a pivotal issue as central governments re-look at the dynamics of their relationship with state and local governments.This study on several ASEAN nations indicates that political centralization is strong as central governments tend to control their sub-national governments. The consolation for these sub-national governments however, is when a nation has economic wealth and increasing growth; then central-local government relations will be enhanced and administrative decentralization is possible.